Construction of a subgenomic BAC library specific for chromosomes 1D, 4D and 6D of hexaploid wheat - Janda, Jaroslav; Bartos, Jan; Safár, Jan; Kubaláková, Marie; Valárik, Miroslav; Cíhalíková, Jarmila; Simková, Hana; Caboche, Michel; Sourdille, Pierre; Bernard, Michel; Chalhoub, Boulos; Dolezel, Jaroslav (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 2004)
The analysis of the hexaploid wheat genome (Triticum aestivum L., 2 n=6 x=42) is hampered by its large size (16,974 Mb/1C) and presence of three homoeologous genomes (A, B and D). One of the possible strategies is a targeted approach based on subgenomic libraries of large DNA inserts. In this work, we purified by flow cytometry a total of 10(7) of three wheat D-genome chromosomes: 1D, 4D and 6D. Chromosomal DNA was partially digested with HindIII and used to prepare a specific bacterial artificial chromosome (BAC) library. The library (designated as TA-subD) consists of 87,168 clones, with an average insert size of 85 kb. Among these clones, 53% had inserts larger than 100 kb, only 29% of inserts being shorter than 75 kb. The coverage was estimated to be 3.4-fold, giving a 96.5% probability of identifying a clone corresponding to any sequence on the three chromosomes. Specificity for chromosomes 1D, 4D and 6D was confirmed after screening the library pools with single-locus microsatellite markers. The screening indicated that the library was not biased and gave an estimated coverage of sixfold. This is the second report on BAC library construction from flow-sorted plant chromosomes, which confirms that dissecting of the complex wheat genome and preparation of subgenomic BAC libraries is possible. Their availability should facilitate the analysis of wheat genome structure and evolution, development of cytogenetic maps, construction of local physical maps and map-based cloning of agronomically important genes.
Keywords: genomová knihovna; chromozomy rostlin; Polyploidy; genom rostlinný; Chromosomes, Plant; Triticum; Genome, Plant; pšenice; mapování chromozomů; Genomic Library; Chromosomes, Artificial, Bacterial; polyploidie; umělé bakteriální chromozomy; Chromosome Mapping